Rating Evaluation of the Quality of Life in Russian Regions - Kuznetsov, Sergey Valentinovich; Rastova, Yuliya Ivanovna; Rastov, Miron Arkadyevich (Economy of Regions, 2017)
In the article, the authors consider the quality of life as an objective and its indicators as the criteria for evaluating the effectiveness of balanced spatial development. The problem of measuring the quality of life has a complex and integrated nature, therefore, we should develop the practice of ratings in its spatial comparisons. The article demonstrates the possibility of using the rating lists of the quality of life of Russian regions by the rating agency “RIA Rating” for 2013-2015 as an information tool for the analysis of the efficiency and effectiveness of the public development of the regional administration. The authors have concluded that with a consecutive growth of an average value of the integrated rating index of quality of life, the different ways of assessing the degree of differentiation of the regions according to the quality of life provide conflicting results. It is necessary to pay attention not so much to ranging and grading of regions as to their classification depending on to the nature of typical problems. Therefore, the rating scale is structured on the basis of the “problematic principle of regional grouping”. The authors have proposed the method of the gradation of the rating scale, allowing to take into account the direction of change of the regions position in the ranking. The relevance of the rating as a key information tool to reduce the regional differentiation of the life quality of the population among the regulatory bodies and civil society will increase if: - it is also used for other subnational entities of the Russian Federation, - there is the use of econometric and computational capabilities of high-tech software systems for a posteriori analysis and models for strategic forecasting of the rankings, - there is the search of a synergistic effect from a variety of estimates of the degree of spatial development.